HEAT SOURCE FOR TIG WELDING MODELLING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A new model of heat source applicable to TIG welding is proposed. The model uses three calibration parameters - efficiency, effective heating spot radius and heat source concentration factor. Based on the experimental results, the model was calibrated and the results obtained for the form of penetration were compared with the experimental ones.